PERADABAN ISLAM DI NUSANTARA - St. Halimang; Rahmawati; A. Amalia Khaerunnisa; Nur As'adi Muayyad; Fiqih Rizki Ardiansyah; Gusti Febrizal; Nur Hasda (STKIP Subang, 2026)
Islamic civilization in the Indonesian archipelago resulted from a gradual process of Islamization, which took place through trade, da'wah, education, marriage, Sufism, and politics. Unlike other regions where Islam spread through military expansion, Islamization in the Indonesian archipelago developed peacefully, prioritizing a cultural approach, enabling adaptation to local traditions. This study aims to analyze the historiography of the arrival of Islam in the Indonesian archipelago, examine the contribution of Islamic civilization in politics, education, and culture, and explain the acculturation process between Islamic teachings and local culture that shaped the characteristics of Indonesian Islam. This study used a library research method with a descriptive-qualitative approach. Data were obtained through literature studies sourced from books, scientific journals, historical documents, and relevant academic literature. Data analysis was carried out through data reduction, data presentation, and systematic drawing of conclusions. The results show that the process of Islamization in the Indonesian archipelago was influenced by various channels, especially trade, Sufism, and education. Islam then formed a new political system through the birth of Islamic sultanates that integrated sharia with customary law. Furthermore, traditional educational institutions such as Islamic boarding schools (pesantren), dayah (dayah), and surau (prayer houses) developed, serving as centers for the transmission of Islamic knowledge. This acculturation resulted in distinctive cultural forms such as the Jawi and Pegon scripts, Islamic-influenced wayang art, mosque architecture, and religious traditions that maintained local values ​​without diminishing the fundamental principles of Islamic teachings. Thus, Islamic civilization in the archipelago demonstrated a moderate, adaptive, and inclusive character, capable of building an Islamic identity that harmonized with the cultural diversity of Indonesian society.